Circulation of influenza A and B in the Czech Republic from 2000-2001 to 2015-2016 - Havlickova, Martina; Druelles, Sophie; Jirincova, Helena; Limberkova, Radomira; Nagy, Alexander; Rasuli, Anvar; Kyncl, Jan (BMC infectious diseases, 2019)
BACKGROUND: To improve national influenza vaccination recommendations, additional data on influenza A and B virus circulation are needed. Here, we describe the circulation of influenza A and B in the Czech Republic during 16 seasons. METHODS: This was a retrospective analysis of data collected from the 2000-2001 to 2015-2016 influenza seasons by the Czech Republic national influenza surveillance network. Influenza was confirmed and viral isolates subtyped by virological assays followed by antigen detection or by reverse transcriptase-polymerase chain reaction. RESULTS: Of 16,940 samples collected, 5144 (30.4%) were influenza-positive. Influenza A represented 78.6% of positive cases overall and accounted for more than 55.0% of all influenza cases in every season, except for 2005-2006 (6.0%). Both A/H1N1 and A/H3N2 were detected in most seasons, except for 2001-2002 and 2003-2004 (only A/H3N2), and 2007-2008 and 2009-2010 (only A/H1N1). Influenza B represented 21.4% of positive cases overall (range, 0.0-94.0% per season). Both influenza B lineages were detected in three seasons, a single B lineage in 11, and no B strain in two. For the 11 seasons where influenza B accounted for ≥20% of positive cases, the dominant lineage was Yamagata in six and Victoria in four. In the remaining season, the two lineages co-circulated. For two seasons (2005-2006 and 2007-2008), the B lineage in the trivalent influenza vaccine did not match the dominant circulating B lineage. CONCLUSIONS: In the Czech Republic, during the 2000-2001 to 2015-2016 influenza seasons, influenza virus circulation varied considerably. Although influenza A accounted for the most cases in almost all seasons, influenza B made a substantial, sometimes dominant, contribution to influenza disease.
Keywords: senioři; Seasons; Lineage; senioři nad 80 let; Population Surveillance; Influenza B virus; Retrospective Studies; kojenec; mladiství; Česká republika; vakcíny proti chřipce; Influenza, Human; Middle Aged; mužské pohlaví; Vaccination; Infant; vakcinace; Adult; mladý dospělý; Influenza Vaccines; Influenza B; Czech Republic; Adolescent; surveillance populace; Influenza A Virus, H3N2 Subtype; dítě; virus chřipky B; Influenza A; virus chřipky A, podtyp H1N1; Child; Influenza A Virus, H1N1 Subtype; Aged, 80 and over; Child, Preschool; Infant, Newborn; Young Adult; ženské pohlaví; novorozenec; retrospektivní studie; předškolní dítě; Humans; virus chřipky A, podtyp H3N2; lidé středního věku; Influenza surveillance; dospělí; Female; Aged; roční období; chřipka lidská; Epidemiology; lidé; Male